Execução de contribuições previdenciárias perante a Justiça do Trabalho - Rossi, Benôni (2005)
The present dissertation brings in its context a critical analysis of the provisions of the part VIII of the article 114 of the Federal Constitution, which attributes to the Labor Justice the competence to enforce, by himself, the social contributions which are foreseen in the article 195, I a e II, of Federal Constitution, resulting from the uttered sentences. In the study there have been pointed conflicts which there are between the way of collecting tributes by the Labor Justice and certain constitutional principles, as the separation of the powers, as the due legal process, as ample defense, as contradictory and isonomy. It has also been demonstrated the incompability of the exercise of that atypical function attributed to the Judge with his main and most important function the jurisdictional enforcement. In order to demonstrate the limits of the competence of the Labor Justice in the enforcement by himself of the social contributions, there is a brief analysis of the elements of the juridical and tributary rule. Only the condemnatory sentences and the sentences which approve judicial accords can produce enforcement in the Labor Justice, that is, those which originate payment in the own process of work. Comments are also made about the Law 10.035 ( 26.10.2000), which establishes procedures to the liquidation and to the enforcement of the social welfare contributions which are in the competence of the Labor Justice. Regarding to the aforesaid legal diploma, the present study remarks that rules from the tributary law have been inserted in the CLT, without observance of what it is decreed in part III of the article 146 of the Federal Constitution, that is, only a complementary law can establish rules about bond, entry and tributary credit. At last, there is a brief study of the institutes of the decadence and of the prescription incident on the law of the federal autarchy, the INSS. The conclusion of the study is that the legislation which attributes to the Labor Justice the obligation of enforcing social contributions should be altered immediately, under penalty of being affected the exercise of the own jurisdictional activity and consequently the institution, the Labor Justice.